EFFECT OF PAIRED FORMATIVE ASSESSMENT ON STUDENTS’ LEARNING - Zia, Qamar; Arif, Nighat; Sadiq, Tahira (Pakistan Armed Forces Medical Journal, 2021)
Objective: To determine the effect of paired formative assessment on students’ learning. Study Design: Quasi experimental study. Place and Duration of Study: Islamic International Medical College Rawalpindi, from Jan 2018 to Jun 2018. Methodology: A total of 160 students who attended otolaryngology module were included in the study. Randomized allocation was done by computerized software programme and students were divided into 2 groups i.e. experimental (group A) and control group (group B). Later on in group A, pairing of students was done by lottery method. Group A and B were dealt with paired and individual formative assessment respectively. Effectiveness of both methods of learning was calculated on the basis of academic scores obtained in tests consisting of 20 MCQs from predefined and taught syllabus. A p-value were obtained by applying independent sample t-test and considered statistically significant at 0.05. Results: Out of 160 participants, 94 (58.7%) were females and 66 (41.3%) were males. In individual testing phase mean scores of group A was 13.36 ± 2.22 and mean scores of group B was 13.24 ± 2.5 (p 0.861). In paired formative assessment phase, mean scores of group A was 16.70 ± 1.94 (CI 95% 2.16-4.55) and mean of scores of group B was 13.40 ± 2.23 (CI 95% 2.16-4.55) p=0.001. Conclusion: The effectiveness of paired formative assessment. This method provides students a conducive environment to achieve learning objectives.